Effects of a school-based lifestyle intervention on ideal cardiovascular health in Chinese children and adolescents: a national, multicentre, cluster-randomised controlled trial. (March 2023) - Guo, Pengfei; Zhou, Yueqin; Zhu, Yanna
Abstract: Background: The prevalence of ideal cardiovascular health among Chinese children and adolescents is alarmingly low. We aimed to examine whether a school-based lifestyle intervention against obesity would improve ideal cardiovascular health. Methods: In this cluster-randomised controlled trial, we included and randomly assigned schools from the seven regions of China to intervention or control (1:1), stratified by province and school grade (grades 1–11; ages 7–17 years). Randomisation was done by an independent statistician. The 9-month intervention consisted of school promotion for diet, exercise, and self-monitor of obesity-related behaviours and the control group was no promotion. The primary outcome, assessed at both baseline and 9 months, was ideal cardiovascular health (six or more ideal cardiovascular health behaviours [non-smoking, BMI, physical activity, and diet] and factors [total cholesterol, blood pressure, and fasting plasma glucose]). We did intention-to-treat analysis and multilevel modelling. This study was approved by the ethics committee of Peking University, Beijing, China (ClinicalTrials.gov, NCT02343588). Findings: 30 629 students in the intervention group and 26 581 students in the control group from 94 schools with any follow-up cardiovascular health measures were analysed. At follow-up, 22·0% (1139/5186) of the intervention group and 17·5% (601/3437) in the control group met ideal cardiovascular health. Overall, the intervention was associated with ideal cardiovascular health behaviours (three or more; odds ratio 1·15; 95% CI 1·02–1·29), but not other ideal cardiovascular health metrics after adjusting for covariates. The intervention had higher effects on ideal cardiovascular health behaviours in primary school students aged 7–12 years (1·19; 1·05–1·34) than secondary school students aged 13–17 years (p<0·0001), with no apparent sex difference (p=0·58). The intervention protected senior students aged 16–17 years from smoking (1·23; 1·10–1·37) and improved ideal physical activity in primary school students (1·14; 1·00–1·30) but was associated with lower odds of ideal total cholesterol in primary school boys (0·73; 0·57–0·94). Interpretation: This school-based intervention, focused on diet and exercise, was effective in improving ideal cardiovascular health behaviours in Chinese children and adolescents. Early intervention might benefit cardiovascular health over the life course. Funding: The Special Research Grant for Non-profit Public Service of the Ministry of Health of China (201202010) and Guangdong Provincial Natural Science Foundation (2021A1515010439).